Phylogenomic analysis of 11 complete African swine fever virus genome sequences - Villiers, Etienne P. de; Gallardo, C.; Arias, Marisa; Silva, M. da; Upton, C.; Martin, R.; Bishop, Richard P. (Elsevier, 2010)
Viral molecular epidemiology has traditionally analyzed variation in single genes. Whole genome phylogenetic analysis of 123 concatenated genes from 11 ASFV genomes, including E75, a newly sequenced virulent isolate from Spain, identified two clusters. One contained South African isolates from ticks and warthog, suggesting derivation from a sylvatic transmission cycle. The second contained isolates from West Africa and the Iberian Peninsula. Two isolates, from Kenya and Malawi, were outliers. Of the nine genomes within the clusters, seven were within p72 genotype 1. The 11 genomes sequenced comprised only 5 of the 22 p72 genotypes. Comparison of synonymous and non-synonymous mutations at the genome level identified 20 genes subject to selection pressure for diversification. A novel gene of the E75 virus evolved by the fusion of two genes within the 360 multicopy family. Comparative genomics reveals high diversity within a limited sample of the ASFV viral gene pool.